PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUTOPLAY PADA TEMA III PEDULI TERHADAP MAKHLUK HIDUP UNTUK KELAS IV SD/MI - Bambang Sudarto; Asri Widiatsih; Fajar isman (Universitas Islam Malang, 2022)
Â The Covid-19 pandemic has greatly impacted the demands for the use of technology in learning which are increasingly high. This study aims to develop an appropriate and effective autoplay-based interactive learning media on the third theme of caring for living things in grade IV SD/MI. The school that became the research site was SD Negeri 1 Kandang Kapongan, Situbondo Regency. The research method used is the development of the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluate). This study uses two validator experts, namely media experts and material experts. The results of the feasibility analysis from media experts and material experts obtained an average value of 86.69% which means it is very feasible. The effectiveness test obtained an average value of 85.90% which means it is very effective.Â